Feminine Stereotypes, Educating Women Trough Literature: An Analysis of Guy de Maupassant Short Stories - Rany Syafrina (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2020)
Guy de Maupassant is a French author whose works have been translated into English. Some of his shorts stories focused on women as the center of the story in which women become the source of misfortune as presented in five chosen short stories for this research. This research is part of objective approach research that focuses on analyzing literary works as it is, without considering the relationship of the intrinsic aspects to the reality of the world. Although the possible intention of the author to use literary work as a tool to educate readers is also explained. In delivering his ideas, Guy de Maupassant often describes women in stereotypes that include formlessness, instability, irrationality, piety, spirituality, materialism. Guy de Maupassant also used his literary work as an instrument to teach the readers about the concept of ideal women by providing advice if not criticism and humiliation; because trough reading literature, the knowledge transfer activities become possible. Keyword: Guy De Maupassant, Short Stories, Stereotypes